2022
DOI: 10.3346/jkms.2022.37.e20
|View full text |Cite
|
Sign up to set email alerts
|

Increased Healthcare Delays in Tuberculosis Patients During the First Wave of COVID-19 Pandemic in Korea: A Nationwide Cross-Sectional Study

Abstract: Background The coronavirus disease 2019 (COVID-19) pandemic caused disruptions to healthcare systems, consequently endangering tuberculosis (TB) control. We investigated delays in TB treatment among notified patients during the first wave of the COVID-19 pandemic in Korea. Methods We systemically collected and analyzed data from the Korea TB cohort database from January to May 2020. Groups were categorized as ‘before-pandemic’ and ‘during-pandemic’ based on TB notificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…3 , 9 As Jinsoo Min et al suggested, this could be due to reassignment of health staff in an overstretched health services during COVID-19, reduced patients referrals and social coughing becoming an stigma. 10 In Italy during the first 3 months of lockdown Francesco Di Gennaro et al described similar findings. 11 However, data regarding Australia reflects a slight increase of TB notifications during this period.…”
Section: Discussionmentioning
confidence: 69%
“…3 , 9 As Jinsoo Min et al suggested, this could be due to reassignment of health staff in an overstretched health services during COVID-19, reduced patients referrals and social coughing becoming an stigma. 10 In Italy during the first 3 months of lockdown Francesco Di Gennaro et al described similar findings. 11 However, data regarding Australia reflects a slight increase of TB notifications during this period.…”
Section: Discussionmentioning
confidence: 69%
“…Second, notification of tuberculosis cases was delayed during the first pandemic. 7,8 However, the delay lasted 6 days, which did not significantly affect annual fluctuations.…”
Section: Discussionmentioning
confidence: 96%
“…The Korean government operated public health emergency level 4 on February 23, 2020 and prioritized most emergency units and hospital rooms for COVID-19 patients. During the first five months of the pandemic, restrictions on tuberculosis treatment were reported in Korea since many pulmonologists had been put on the frontlines 39 . Women, urban dwellers, and individuals without chronic diseases experience delays in health screening and non-urgent medical visits 40 .…”
Section: Discussionmentioning
confidence: 99%